Cone-beam computed tomography assessment of root canal transportation and evaluation of canal centering using Protaper Gold, XP Endoshaper, and Edgefile X7 - Tushar Kanti Majumdar; Minakshi Chowdhury; Sayantan Mukherjee; Paromita Mazumdar (Wolters Kluwer Medknow Publications, 2022)
Aim: This study aims to access and evaluate canal transportation and canal centering ability of Protaper Gold (PTG), XP EndoShaper (XPS) and EdgeFile X7 using cone-beam computed tomography (CBCT). Materials and Methods: Sixty freshly extracted single-rooted premolars with mature apex and a canal curvature of 10°-20° were chosen and arbitrarily divided into three experimental groups (n = 20). After decoronation, the teeth measuring 16 mm were included in the study for standardization. According to the manufacturer's instructions, canals were shaped with PTG in Group 1, XPS in Group 2 and EdgeFile X7 in Group 3. For the evaluation of the root canal transportation at 2 mm, 4 mm, and 6 mm from the apex, canals were scanned before and after instrumentation using CBCT scanner. Independent t-tests and one-way ANOVA were used to analyze data and significance level was set at P < 0.05. Results: XPS showed significantly lower canal transportation than PTG system. Moreover, the centering ability of the XPS significantly higher than EdgeFile X7 and PTG at all root levels (P < 0.05). Conclusion: The XPS and EdgeFile X7 rotary file system showed the lowest transportation in both mesiodistal and buccolingual directions and also the highest centering ability. The PTG file showed the highest transportation and lowest centering ability.